Solar radiation prediction using boosted decision tree regression model: A case study in Malaysia - Jumin E.; Basaruddin F.B.; Yusoff Y.B.M.; Latif S.D.; Ahmed A.N. (Springer Science and Business Media Deutschland GmbH, 2023)
artificial intelligence; artificial neural network; numerical model; prediction; regression analysis; solar power; solar radiation; Malaysia; algorithm; artificial intelligence; decision tree; Malaysia; solar energy; Algorithms; Artificial Intelligence; Decision Trees; Malaysia; Neural Networks, Computer; Solar Energy